Pleasure in profit : popular prose in seventeenth-century Japan - Moretti, Laura (Lecturer in Pre-modern Japanese Studies) (Columbia University Press, 2020)
"The late seventeenth century was a time of peace in Japan, and consequently, schools and culture flourished even for non-elites. Although publishing for vernacular-only (i.e., not literary Sinitic) readers was big business, both Japanese and Western scholarship has largely ignored these books, concentrating instead on a narrative of the development of the novel in the seventeenth century, culminating in the writings of Ihara Saikaku (1642-1693). In Pleasure in Profit, Laura Moretti studies lowbrow seventeenth-century literature on its own terms, and in doing so, not only presents a much more accurate picture of prose at this time but also contributes to our understanding of Japanese non-elites--for instance, how key principles of Buddhism and Confucianism spread to the populace--and comparative popular culture, showing that this literature was no different from the French bibliothèque bleue, British chapbooks, or the Russian literature of lubok"--